Laser resurfacing today and the 'cook book' approach: a recipe for disaster? - Trelles, M A (Journal of cosmetic dermatology, 2004)
Background  Laser ablative skin resurfacing achieves skin rejuvenation by precise ablation of photoaged skin and subsequent re‐epithelialisation and dermal remodelling. Carbon dioxide (CO2) and Erbium:YAG (Er:YAG) lasers are the established choice. A wide range and many sets of parameters have been proposed as the gold standard for each system but results have varied. Aims  To show that this single system ‘cook book’ approach must be rejected in favour of a more comprehensive approach. Subjects and methods  The author has experience of ablative skin resurfacing in over 1200 patients and has used both systems. A more flexible approach, using a combined wavelength system, is presented. It comprises precise ablation of the epidermal with the Er: YAG (to create an epidermal window), followed instantaneously with subablative heating of the exposed dermis with the CO2 laser. Results  Since adopting the dual wavelength/dual modality approach, more than 600 patients have been treated, with excellent results and a very high patient satisfaction index, currently around 90%, obtained from the sum of the very satisfied and satisfied patients using a five‐grade scale. Possible resurfacing‐related complications have included prolonged erythema, hyper or hypopigmentation, scarring and viral infections, which were more common with single system resurfacing. The author's complication rate remains under 1%, without any prophylactic use of antiviral agents. Conclusions  The cook book approach, whereby a particular set of fixed laser resurfacing parameters for a specific single laser system are adopted and rigidly applied in all patients, will not achieve the best treatment effects and may even produce a bad result and dissatisfied patients. The dual modality approach allows a combination of the favourable elements of each of the two wavelengths with excellent and consistent results.